Is the Threat of Reemployment Services More Effective Than the Services Themselves? Evidence from Random Assignment in the UI System - Black, Dan A; Smith, Jeffrey A; Berger, Mark C; Noel, Brett J (American Economic Review, 2003)
We examine the effect of the Worker Profiling and Reemployment Services system. This program “profiles” Unemployment Insurance (UI) claimants to determine their probability of benefit exhaustion and then provides mandatory employment and training services to claimants with high predicted probabilities. Using a unique experimental design, we estimate that the program reduces mean weeks of UI benefit receipt by about 2.2 weeks, reduces mean UI benefits received by about $143, and increases subsequent earnings by over $1,050. Most of the effect results from a sharp increase in early UI exits in the treatment group relative to the control group.